The changes in semen quality, arginase activity and nitric oxide level in dexamethasone-treated rams - Kaya, Seyma Ozer; Erisir, Mine; Gur, Seyfettin; Kandemir, Fatih Mehmet; Benzer, Fulya; Kaya, Emre; Turk, Gaffari (Wiley, 2020)
This study was made to investigate the effects of intramuscular administrations of dexamethasone on seminal plasma nitric oxide levels and arginase activity, and some spermatological parameters in rams. Ten Akkaraman rams weighing 50-60 kg and 2 years old were used as material in this study. The study was performed during the breeding season (September-November) for rams. The semen was collected by artificial vagina at 1st, 4th, 24th, 48th, 72nd and 96th hours for control group before dexamethasone administration. For treatment group, 0.25 mg/kg dexamethasone was administered and semen was collected at the time points described for control group. Spermatological characteristics of semen samples (semen volume, pH, sperm motility, density and abnormal sperm rate), seminal plasma arginase enzyme activities and nitric oxide levels were determined. It was determined that the administration of dexamethasone was detected to decrease seminal plasma arginase activity (p < .05 and .01) and nitric oxide level (p < .05), semen volume (p < .05 and .01), mass activity (p < .05 and .01), sperm density (p < .05) and sperm motility (p < .05 and .01), and to increase abnormal sperm rate (p < .05 and .01). In conclusion, dexamethasone is not recommended to be used during the breeding season as it damages the sperm quality of the rams.
Keywords: arginase activity; dexamethasone; nitric oxide; ram; semen quality